IMPROVING PHYSICAL FITNESS THROUGH THE OUTDOOR ADVENTURE EDUCATION PROGRAM IN PHYSICAL EDUCATION IN HIGH SCHOOL - Setiawan, Ikhwan; Sukur, Abdul; Hernawan; Subandi, Oman Unju (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This research aims to find the effectiveness of the Physical Education learning model through the Outdoor Adventure Education Program to improve physical fitness for high school students. The research design using a pre-experimental method in the form of a one group pretest-posttest design, two groups that are given a pretest and a posttest, the experimental group is given sixteen times treatment to determine the effect of the program on increasing students' physical fitness. 60 respondents divided into 30 experimental group respondents and 30 control group respondents. Physical fitness test instruments involve: (1) Hand Eye Coordination test, (2) Vertical Jump Test, (3) T-Test, (4) Hand Touch Reaction Test, (5) Dipping Test, and (5) Beep Test, the test based on Test guidelines Indonesian Student Fitness from the Ministry of Education and Culture. the results of the effectiveness test for the Experimental class were 67% in the quite effective interpretation category , the effectiveness test results for the control class were 21% in the less effective interpretation category. The test results for the difference in average physical fitness showed that the value was p = 0.000 < 0.05 . This study shows that there is a significant average difference between the experimental group and the control group.